Adoption of the Transparency and Openness Promotion (TOP) guidelines within health psychology and behavioural medicine journal policies: a cross-sectional study - Toomey, Elaine; Coyne, Rory; Derksen, Christina; Grant, Sean P.; Jones, Christopher; Kijowska, Marta; McNeill, Ilona; Naughton, Felix; O’Mahony, Aoife; Norris, Emma (Health psychology review, 2025)
Scientific journals play a crucial role in promoting open science. The Transparency and Openness Promotion (TOP) guidelines identify a range of standards that journals can adopt to promote the verifiability of the research they publish. We evaluated the adoption of TOP standards within health psychology and behavioural medicine journal policies, as this had not yet been systematically assessed. In a cross-sectional study on 19 health psychology and behavioural medicine journals, eight raters evaluated TOP standard adoption by these journals using the TRUST journal policy evaluation tool. Out of a total possible score of 29, journal scores ranged from 1 to 13 (median = 6). Standards related to use of reporting guidelines and data transparency were adopted the most, whereas standards related to pre-registration of study analysis plans and citation of code were adopted the least. TOP guidelines have to-date been poorly adopted within health psychology and behavioural medicine journal policies. There are several relatively straightforward opportunities for improvement, such as expanding policies around research data to also consider code and materials, and reducing ambiguity of wording. However, other improvements may require a collaborative approach involving all research stakeholders.